(untitled) (KULT_online, 2017)
The volume Exile und Shoah, edited by Bettina Bannasch, Helga Schreckenberger, Alan E. Steinweis, Doerte Bischoff, Claus-Dieter Krohn, and Lutz Winkler provides the reader with a synthesis of research on exile and the study of the Shoah. With the aid of an interdisciplinary approach the volume shows the interplay between the personal experiences of German-speaking exiles and their scientific and literary work that often helped them cope with traumas they suffered. By changing between general illustrations of the exile and concrete examples of biographies, the edition not only covers the current state of research but also offers new questions and approaches in the study of exile and Shoah.